2018
DOI: 10.3389/fpsyg.2018.00423
|View full text |Cite
|
Sign up to set email alerts
|

Mood Detection in Ambiguous Messages: The Interaction Between Text and Emoticons

Abstract: Face-to-face communication has several sources of contextual information that enables language comprehension. This information is used, for instance, to perceive mood of interlocutors, clarifying ambiguous messages. However, these contextual cues are absent in text-based communication. Emoticons have been proposed as cues used to stress the emotional intentions on this channel of communication. Most studies have suggested that their role is to contribute to a more accurate perception of emotions. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In short, our study is consistent with previous neuroimaging and brain injury studies (Shamay-Tsoory et al, 2003 , 2009 ; Lawrence et al, 2006 ; Schulte-Rüther et al, 2007 , 2008 ; Pfeifer et al, 2008 ; Smith et al, 2015 ; Massey et al, 2017 ) and confirms the important role of the IFG in cognitive empathy and the effective role of HD-tDCS in regulating social cognitive functioning. Notably, our results also show that participants responded to negative emotional pictures longer than positive emotional pictures during cognitive empathic tasks consistent with previous studies (Leppänen and Hietanen, 2004 ; Song et al, 2017 ; Aldunate et al, 2018 ). Earlier findings have shown that during emotional recognition, happiness is recognized faster than sadness (Crews and Harrison, 1994 ; Leppänen and Hietanen, 2004 ), anger (Hugdahl et al, 1993 ) and disgust (Stalans and Wedding, 1985 ).…”
Section: Discussionsupporting
confidence: 93%
“…In short, our study is consistent with previous neuroimaging and brain injury studies (Shamay-Tsoory et al, 2003 , 2009 ; Lawrence et al, 2006 ; Schulte-Rüther et al, 2007 , 2008 ; Pfeifer et al, 2008 ; Smith et al, 2015 ; Massey et al, 2017 ) and confirms the important role of the IFG in cognitive empathy and the effective role of HD-tDCS in regulating social cognitive functioning. Notably, our results also show that participants responded to negative emotional pictures longer than positive emotional pictures during cognitive empathic tasks consistent with previous studies (Leppänen and Hietanen, 2004 ; Song et al, 2017 ; Aldunate et al, 2018 ). Earlier findings have shown that during emotional recognition, happiness is recognized faster than sadness (Crews and Harrison, 1994 ; Leppänen and Hietanen, 2004 ), anger (Hugdahl et al, 1993 ) and disgust (Stalans and Wedding, 1985 ).…”
Section: Discussionsupporting
confidence: 93%
“…They could show reaction times where shorter for happy faces than for angry faces, but no significant results could be found by comparing real faces to cartoon faces. Moreover, results by Aldunate et al (2018) suggested, that participants reacted faster to positive emoticons compared to negative ones. These results indicate that not the stimulus type plays a crucial role in terms of reaction times, but valence.…”
Section: Introductionmentioning
confidence: 94%
“…While our study shows behavioral and neurophysiological effects of psychosocial stress during the performance of a cognitive task, it is an open question to understand how stress can affect the processing of stimuli with emotional valence (Aldunate et al, 2018), or what the mechanisms are that underly the stress effects over top-down or bottom-up attentional modulations. In summary, our study presents a multilevel perspective for an integrative understanding of the mechanisms underlying psychosocial stress and attentional control.…”
Section: Discussionmentioning
confidence: 88%